2016
DOI: 10.1063/1.4963305
|View full text |Cite
|
Sign up to set email alerts
|

Markov state model of the two-state behaviour of water

Abstract: With the help of a Markov State Model (MSM), two-state behaviour is resolved for two computer models of water in a temperature range from 255 K to room temperature (295 K). The method is first validated for ST2 water, for which the so far strongest evidence for a liquid-liquid phase transition exists. In that case, the results from the MSM can be cross-checked against the radial distribution function g(5)(r) of the 5th-closest water molecule around a given reference water molecule. The latter is a commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 56 publications
(111 reference statements)
1
39
0
Order By: Relevance
“…These new analyses, applied to novel and old simulation data, show that water molecules differing in their local environment can be treated as species in chemical equilibrium. Interestingly, the ability to resolve these classes requires information on the degree on translational order of the second-nearest-neighbor shell (31), sophisticated Markov state models (32), and, in some cases, the suppression (33) of the vibrational (translational and librational) component via the inherent structure methodology (34).…”
Section: Liquid Watermentioning
confidence: 99%
“…These new analyses, applied to novel and old simulation data, show that water molecules differing in their local environment can be treated as species in chemical equilibrium. Interestingly, the ability to resolve these classes requires information on the degree on translational order of the second-nearest-neighbor shell (31), sophisticated Markov state models (32), and, in some cases, the suppression (33) of the vibrational (translational and librational) component via the inherent structure methodology (34).…”
Section: Liquid Watermentioning
confidence: 99%
“…The Markov state model used to analyse of the protein solvation layer has been constructed in essentially the same way as in Ref. 62, where the two-state behaviour of bulk water has been investigated. In brief, the five closest water molecules around a given reference water molecule were selected.…”
Section: B Markov State Modelmentioning
confidence: 99%
“…In comparison to Ref. 62, the algorithm had to be adapted only to a minor extent for the purpose of the present study. That is, since the structures of the five closest water molecules around a given water molecule need to be analyzed with regard to the question whether it is HDL or LDL-like, it does not make sense to consider reference water molecules in the first solvation layer around the protein, since those necessarily will have a smaller coordination number.…”
Section: B Markov State Modelmentioning
confidence: 99%
“…For example, partitioning the conformational space for defining the microstates is a necessary stage for Markov state approaches (MSM). Hamm studied the two‐state water behavior, clustering microstates of waters via MSM . Da et al studied the backtracking process of RNA Polymerase II by MSM, dividing MD samples into 800 states by k ‐centers clustering .…”
Section: Introductionmentioning
confidence: 99%
“…Hamm studied the two-state water behavior, clustering microstates of waters via MSM. [44] Da et al studied the backtracking process of RNA Polymerase II by MSM, dividing MD samples into 800 states by k-centers clustering. [45] Zhao et al developed a parallel k-center clustering method and identified states of biomolecule.…”
Section: Introductionmentioning
confidence: 99%